Do Local Political Elections Affect Daily Stock Returns? Evidence From the Republic of North Macedonia's MBI10 Index - Deari, Fitim; Koku, Paul Sergius (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
Even though “all politics” are supposedly “local”, as reportedly said Tip O’Neil, the majority of studies on the link between politics and finance focused on presidential elections. This argues that overlooking local elections could result in a gap in the literature, thus it focused on the effect of the 2021 local elections on the stock market in the Republic of North Macedonia. The results could not reject the null hypothesis that local elections did not have any statistically significant effect on the stock prices as only 10% of the stocks traded experienced significant abnormal returns during the election period.